The Influence of Psychological Capital, Certification Status and Work Resources on Teachers Performance - Muh Adnan Hudain; Fitria Khasanah; Susatyo Adhi Pramono; Dede Haryanto; Ilham Kamaruddin (Journal on Education, 2023)
This study's objective is to ascertain how self-efficacy, optimism, hope, and social support affect all aspects of a teacher's profession, including their autonomy, connection with superiors, performance evaluations, and certification status. The sample for this study included 859 high school teachers. With a non-probability selection process, 230 teachers were chosen. Use confirmatory factor analysis (CFA) techniques to assess the accuracy of measurement tools. Using multiple regression to examine research data. The results of the study show that numerous elements, such as self-efficacy, optimism, hope, resilience, social support, the nature of a teacher's connection with superiors, autonomy, performance assessment, and teacher certification status, have a significant impact on all of a teacher's work. The results of the study show that all independent factors can explain 49% of the variance in the overall amount of work, while variables not included in the study have an impact on the remaining 51%. According to the results of the hypothesis testing, hope, optimism, and self-efficacy all significantly affect how well an individual performs at work.